Sea surface temperatures of sediment core DCR-1PC and sub-surface temperatures of sediment core MD19-3575CQ resampled at a 3 kyrs interval - Matthieu Civel-Mazens; Xavier Crosta; Giuseppe Cortese; Vikki Lowe; Minoru Ikehara; Takuya Itaki; Karen E Kohfeld (PANGAEA, 2024)
The SST records of core DCR-1PC (Crosta et al., 2020) and the subST records of cores MD19-3575CQ (this study) were resampled at a 3kyrs interval to substract subST to SST. This allowed to reconstruct the evolution of the delta of temperature (deltaT) between surface and subsurface. We here include the resampled and deltaT records.
In: Civel-Mazens, M et al. (2024): Sediment cores MD19-3575CQ, MD19-3580, COR-1PC, PS2606-6 - subsurface, surface temperature (full resolution and resampled), and DeltaT records [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.973478